The Dynamics of Self-Disclosure among Gay and Transgender Individuals in the Indonesian Social Context - Maria, Anna; Rahayu, Maria Nugraheni Mardi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Self-disclosure is the process by which individuals reveal their personal identity to others. For gay and transgender individuals, self-disclosure presents challenges due to social stigma. This study aims to understand the self-disclosure experiences of gay and transgender individuals and the factors influencing this process. This research employs a qualitative method with a phenomenological design. The participants consisted of two individuals identifying as gay and transgender, selected using the snowball sampling technique. Data were collected through in-depth interviews and analysed using thematic analysis The results indicate that self-disclosure is a gradual process influenced by both internal and external factors. The primary obstacles to self-disclosure include fear of stigma, experiences of bullying, and anxiety about social reactions. However, social support from friends, colleagues, and inclusive environments can help individuals feel more confident in revealing their identities. The key factors affecting self-disclosure include the level of trust in the recipient, group size, dyadic effects, and supportive environments. This study provides insight into the dynamics of self-disclosure among gay and transgender individuals and highlights the crucial role of social support in creating a safe environment for them. The implications of this research can be utilized to raise awareness among families, professionals, and society in fostering open and non-judgmental communication. Self-disclosure merupakan proses individu dalam mengungkapkan identitas pribadinya kepada orang lain. Bagi individu gay dan transgender, self-disclosure menjadi tantangan karena adanya stigma sosial. Penelitian ini bertujuan untuk memahami pengalaman self-disclosure pada individu gay dan transgender serta faktor-faktor yang memengaruhi proses tersebut. Penelitian ini menggunakan metode kualitatif dengan desain fenomenologis. Partisipan terdiri dari dua individu yang mengidentifikasi sebagai gay dan transgender, yang dipilih dengan teknik snowball sampling. Data diperoleh melalui wawancara mendalam dan dianalisis menggunakan metode analisis tematik. Hasil penelitian menunjukkan bahwa self-disclosure merupakan proses bertahap yang dipengaruhi oleh faktor internal dan eksternal. Hambatan utama dalam self-disclosure adalah ketakutan terhadap stigma, pengalaman perundungan, serta kecemasan terhadap reaksi lingkungan. Namun, dukungan sosial dari teman, kolega, dan lingkungan yang inklusif dapat membantu individu lebih percaya diri dalam mengungkapkan identitasnya. Faktor utama yang memengaruhi self-disclosure adalah tingkat kepercayaan terhadap penerima informasi, ukuran kelompok, efek diadik, dan lingkungan yang mendukung. Penelitian ini memberikan wawasan mengenai dinamika self-disclosure pada individu gay dan transgender serta menyoroti pentingnya peran dukungan sosial dalam menciptakan lingkungan yang aman bagi mereka. Implikasi dari penelitian ini dapat digunakan untuk meningkatkan kesadaran keluarga, tenaga profesional, serta masyarakat dalam membangun komunikasi yang terbuka dan tidak menghakimi.